2019
DOI: 10.1073/pnas.1910073116
|View full text |Cite|
|
Sign up to set email alerts
|

A single combination gene therapy treats multiple age-related diseases

Abstract: SignificanceHuman and animal longevity is directly bound to their health span. While previous studies have provided evidence supporting this connection, therapeutic implementation of this knowledge has been limited. Traditionally, diseases are researched and treated individually, which ignores the interconnectedness of age-related conditions, necessitates multiple treatments with unrelated substances, and increases the accumulative risk of side effects. In this study, we address and overcome this deadlock by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…In a recent pioneering study, Davidsohn et al [132] showed in mice that a single delivery of three longevity associated genes, including fibroblast growth factor 21 (FGF21), αKlotho, and a soluble form of mouse transforming growth factor-β receptor 2 (sTGFβR2) using adeno-associated viruses can mitigate four age-related diseases: obesity, type 2 diabetes, heart failure, and renal failure. These results emphasize the promise of gene therapy for the treatment of diverse age-related ailments.…”
Section: Future Directionsmentioning
confidence: 99%
“…In a recent pioneering study, Davidsohn et al [132] showed in mice that a single delivery of three longevity associated genes, including fibroblast growth factor 21 (FGF21), αKlotho, and a soluble form of mouse transforming growth factor-β receptor 2 (sTGFβR2) using adeno-associated viruses can mitigate four age-related diseases: obesity, type 2 diabetes, heart failure, and renal failure. These results emphasize the promise of gene therapy for the treatment of diverse age-related ailments.…”
Section: Future Directionsmentioning
confidence: 99%
“…In fact, three-fold overexpression of TGFβ in mice caused glomerulosclerosis and albuminuria (59). More recently, administration of a soluble TGFβ receptor II by a gene therapy protocol to mice with renal fibrosis, where TGFβ contributes to the pathology, showed significant beneficial effects (60). These results conclusively demonstrate a significant pathologic role of TGFβ in renal diseases, suggesting blocking of TGFβ may be beneficial in renal fibrosis.…”
Section: Discussionmentioning
confidence: 91%
“…Whilst the modulation of Klotho expression in transgenic mice has been shown to extend lifespan by up to 30%, it is increasingly recognised that prevention or treatment of these diseases may involve the perturbation of multiple genetic pathways [2,139,140]. Taking this in to consideration, Davidsohn and colleagues undertook an in vivo study to evaluate gene therapies based on three longevity associated genes (fibroblast growth factor 21 [FGF21], Klotho, the soluble form of the mouse transforming growth factor receptor 2 [sTGFβR2]) delivered individually and in combination using AAV, and explored their ability to alleviate four age-related diseases-obesity, type II diabetes, heart failure, and renal failure [141]. They observed that a single formulation combining two separate gene therapies into a single agent was able to treat all four diseases.…”
Section: Therapeutic Approaches To Klotho Deliverymentioning
confidence: 99%